Tailoring morphological and chemical properties of covalent triazine frameworks for dual CO2 and H2 adsorption. (12th February 2022) - Tuci, Giulia; Iemhoff, Andree; Rossin, Andrea; Yakhvarov, Dmitry; Gatto, Marco Filippo; Balderas-Xicohténcatl, Rafael; Zhang, Linda; Hirscher, Michael; Palkovits, Regina; Pham-Huu, Cuong; Giambastiani, Giuliano
Abstract: The development of functional porous samples suitable as gas-adsorption materials is a key challenge of modern materials chemistry to face with global warming or issues related to renewable energy-storage solutions. Herein, a set of five Covalent Triazine Frameworks (CTFs) featured by high specific surface area (SSA, up to 3201 m 2  g −1 ) and N content as high as 12.2 wt% have been prepared through a rational synthetic strategy and exploited with respect to their gas uptake properties. Among CTFs from this series, CTF- p DCB/DCI HT (4 ) combines ideal morphological and chemico-physical properties for CO2 and H2 adsorption. Noteworthy, besides ranking among CTFs with the highest CO2 adsorption capacity reported so far (up to 5.38 mmol g −1 at 273 K and 1 bar), 4 displays a H2 excess uptake at 77 K of 2.84 and 5.0 wt% at 1 and 20 bar, respectively, outperforming all CTF materials and 2D Porous Organic Polymers of the state-of-the-art . Graphical abstract: Image 1 Highlights: Highly porous N-rich CTF materials are prepared by mixing different building blocks. CTFs chemical and morphological properties are optimized for dual CO2 /H2 adsorption. CTF from this series offers the highest H2 uptake value reported for organic polymers.